La defensa del territorio en México: una apuesta por la vida desde el Concejo Indígena de Gobierno (CIG) al Congreso Nacional Indígena (CNI) [Tema Central] - García Jiménez, Susana (2025)
Historically, indigenous peoples have led the struggles and resistance in defense of territory as a space that enables the reproduction of life in an integral, economic, political, social and cultural way in the face of the capitalist vision that territory is equal to land, a mere repository of natural resources and a source of wealth. This article aims to show how the National Indigenous Congress (CNI) and the Indigenous Council of Government (CIG) represent a project for the defense of territory and life, incorporating in their struggles the participation of diverse actors and where the role of women is vindicated in the light of an inclusive discourse, of equity of justice and that looks down and to the left. To carry out this analysis we used a documentary analysis and an ethnography of the documents issued by the CNI and CIG to show the dissident position of the neoliberal discourse regarding the territory. At the same time, we recovered some theoretical aspects regarding territory and its relationship with the reproduction or denial of life. Therefore, the declarations, actions and struggles of both the CNI and the CIG are relevant, since they bring together different native peoples.